Platelet Rich Plasma as Monotherapy in Androgenetic Alopecia - Singh, Amar; Pant, Astha; Saini, Sumeet Pal (Journal of Neonatal Surgery, 2025)
Introduction. We aimed to know the effect of PRP therapy in androgenetic alopecia and to determine the degree of response to platelet-Rich plasma in various grades of androgenetic alopecia. Methods. This hospital-based pilot study was conducted in Department of Dermatology, Venereology and Leprosy Shri Guru Ram Rai Institute of Medical and Health Sciences, Patel Nagar, Dehradun during November 2014 to May 2017. Subjects with in the age 18-40 years, under Hamilton-Norwood classification 1-4 for male pattern baldness, Ludwig alopecia score 1-2 for female pattern baldness were included in the study. After taking history and general examination and routine blood tests and serology was done in all subjects. PRP was prepared by collecting 20 ml of patient’s venous blood in Sodium citrate vial and centrifuged at 3000 rpm for 15 minutes to obtain plasma, buffy coat and RBC layer. The plasma and buffy coat were aspirated and again centrifuged at 2000 RPM for next 10 minutes to further obtain reduced volume of PRP by ¼ settled at the bottom. PRP was activated by addition of calcium gluconate by 9:1 and injected by insulin syringes two units intradermal 1 cm apart at 0.5 cm depth in alopecic area monthly for 6 months. Results.The mean of hair pull test before study was 5.44 ± 2.75 which reduced to 0.38±0.62 after completion of 6 sessions. Further post hoc analysis showed significant improvement was noted between hair pull test results before therapy and at 3 months (p<0.0001) and at 6 months (p=0.007). The mean hair density before treatment was 96.54±24.99 which increased to 106.92±28.04/cm2. Further post hoc analysis showed significant improvement was noted between hair density results before therapy and at 3 months (p<0.0001) and at 6 months (p<0.0001). Also, significant improvement was noted at 6 months of follow up compared to 3 months of follow up (p<0.0001). Conclusion. Role of PRP in androgenetic alopecia is an emerging treatment but there is lack of data about its efficacy. We lack a comparative group with placebo or with some other treatment like PRP with minoxidil or finasteride.